Natural flavonoids: Potential therapeutic strategies for non-alcoholic fatty liver disease - Tan, Panli; Jin, Li; Qin, Xiang; He, Beihui (Frontiers in Pharmacology, 2022)
The incidence of nonalcoholic fatty liver disease (NAFLD) is increasing rapidly worldwide, but there are limited treatments of NAFLD currently. The disease spectrum includes simple fatty liver, nonalcoholic steatohepatitis (NASH), fibrosis, cirrhosis, and even progress to hepatocellular carcinoma (NASH-HCC). Currently, the therapeutic effect of NAFLD is still controversial. Although researchers have conducted certain studies on the pathogenesis of NAFLD, the pathogenesis and anti-NAFLD mechanisms have not been fully revealed. Previous studies have found that flavonoids, as a natural substance with extensive pharmacological activity and good therapeutic effect, have excellent performance in antioxidant, anti-inflammatory, metabolic disease improvement, anti-tumor and other aspects, and can significantly alleviate NAFLD. Flavonoids may be further developed as therapeutic drugs for NAFLD. In this paper, the pathogenesis of NAFLD and the mechanisms of flavonoids against NAFLD were summarized, in order to provide some theoretical basis for screening flavonoids against non-alcoholic liver injury.